The role of Nuclear Erythroid Factor 2 (Nrf-2) in vascular reactivity of normotensive and spontaneously hypertensive rats (Research, Society and Development, 2022)
The uncontrolled production of the reactive oxygen species (ROS) generates oxidative stress and the development of chronic diseases, such as hypertension. Antioxidant enzymes can reduce the cellular level of ROS. Nuclear erythroid factor 2 (Nrf-2) favors the expression and activity of antioxidant enzymes. In hypertensive rats, Nrf-2 expresssion appears to be reduced in blood vessels and, consequently, it favors the oxidative stress and vascular dysfunction. Apocynin (APO) has been considered a new antioxidant drug. APO reduces blood pressure, decreases ROS production, and improves endothelial function in spontaneously hypertensive rats (SHR). We hypothesized that the role of Nrf-2 in vascular reactivity is altered in SHR and APO-treatment prevents this alteration. To test this hypothesis, we evaluated aorta reactivity to phenylephrine (PE) and acetylcholine (ACh), in the absence and presence of Brusatol, Nrf-2 inhibitor. We used aortas from normotensive Wistar rats and SHR, untreated or treated with APO. Brusatol increased the reactivity of the aortas from SHR to PE, but did not change the reactivity of Wistar rat aortas. In APO-treated SHR aortas, the effect of Brusatol was not observed. The vasodilator responses to ACh were not modified by Brusatol in aortas from normotensive or hypertensive rats, untreated or treated with APO. These results suggest that Nrf-2 is activated in the contractile response to PE. In SHR aortas, exacerbated generation of ROS induces the activation of Nrf-2. This suggestion is reinforced by the lack of Brusatol effect in APO-treated SHR aortas. As APO is an antioxidant drug, the reduction of ROS in vascular cells would not lead to Nrf-2 activation.